The drivers of housing cycles in Spain - Oriol Aspachs-Bracons; Pau Rabanal (SERIEs - Journal of the Spanish Economic Association, 2010)
In the last 15 years, Spain has witnessed a large increase in housing prices and in the importance of the housing sector, which has refreshed the debate on the drivers of housing cycles. Since Spain joined the European Monetary Union (EMU), twomain important factors behind the housing boom appear to be the decrease of nominal interest rates due to the disappearance of currency risk premia, and demographic factors related to immigration and changing patterns in household composition. In order to assess the importance of these and other factors, in this paper we estimate a New Keynesian model of a currency area with durable goods, using data for Spain and the rest of the EMU. We find that parameter estimates are similar to the ones estimated in the literature, in that, in particular, durable goods prices are more flexible than nondurable consumption goods. We find that housing demand and technology shocks are the main driver of the recent housing boom. Finally, we examine the role of different rigidities suggested in the literature to help the model fit the data.We find that labor market frictions, that in the model imply costly labor reallocation across sectors, are crucial to explain main features of the data. On the other hand, financial frictions that impose a collateral constraint on borrowing do not appear to be relevant.
Keywords: E44; E52; F41; 330; housing; monetary policy; financial constraints; Immobilienmarkt; Neukeynesianische Makroökonomik; Eurozone; Spanien